2004
DOI: 10.1007/s10038-004-0186-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of gene therapy in Gaucher disease using an adeno-associated virus vector

Abstract: Gaucher disease, one of the common lysosomal storage disorders, is caused by a deficiency of glucocerebrosidase (GC). We investigated gene transfer using recombinant adeno-associated viral (rAAV) vectors containing human GC cDNA driven by the human elongation factor 1-a promoter. This rAAV vector mediated efficient expression of human GC in human Gaucher fibroblasts. GC activities were increased from 2.8 to 3.4 times in normal fibroblast and from 1.9 to 4.6 times in Gaucher fibroblasts, and these increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Initially thought to be of great promise for Gaucher disease patients, clinical trials applying hematopoietic stem cell-mediated gene therapy to ameliorate Gaucher disease type 1 were only successful in a minority of the patients [108], although it is important to realize that with continued improvements this therapy may become viable. Much progress has been made in the design of improved vectors including recombinant adeno-associated viral vectors [109] and HIV-1-based lentivirus vectors [110] that express human GC cDNA. Mice transplanted with lentivirus-transduced bone marrow-derived hematopoietic stem cells overexpressing human GC exhibited relatively high levels of GC activity in various tissues including bone marrow and spleen, but also the brain, 2-6 months after transplantation [111].…”
Section: Other Therapeutic Strategies For Gaucher Diseasementioning
confidence: 99%
“…Initially thought to be of great promise for Gaucher disease patients, clinical trials applying hematopoietic stem cell-mediated gene therapy to ameliorate Gaucher disease type 1 were only successful in a minority of the patients [108], although it is important to realize that with continued improvements this therapy may become viable. Much progress has been made in the design of improved vectors including recombinant adeno-associated viral vectors [109] and HIV-1-based lentivirus vectors [110] that express human GC cDNA. Mice transplanted with lentivirus-transduced bone marrow-derived hematopoietic stem cells overexpressing human GC exhibited relatively high levels of GC activity in various tissues including bone marrow and spleen, but also the brain, 2-6 months after transplantation [111].…”
Section: Other Therapeutic Strategies For Gaucher Diseasementioning
confidence: 99%
“…However, it has been largely unsuccessful to date in human patients, although GlcCer storage can be significantly reduced in cultured cells by gene transfer. For instance, recombinant adeno‐associated viral vectors containing human GlcCerase driven by the human elongation factor 1‐α promoter have recently been used and shown to elevate GlcCerase levels in both normal and Gaucher fibroblasts (Hong et al , 2004); moreover, intravenous administration of vectors to wild‐type mice resulted in increased GlcCerase activity that persisted for over 20 weeks. Other vectors have been used (i.e.…”
Section: Gene Therapymentioning
confidence: 99%
“…Subsequent clinical studies showed that the transduction efficiency and engraftment of autologous stem cells from Gaucher patients occurred with insufficient efficiency for therapeutic efficacy [13]. More recently, adenoviral [14], lentiviral [15], and adeno-associated viral (AAV) vectors [16] harboring the human glucocerebrosidase (hGC) cDNA have also been evaluated, though none in a systemic animal model of Gaucher disease. Compared to other viral-based vectors, AAV vectors offer some advantages for the treatment of Gaucher disease [17][18][19].…”
Section: Introductionmentioning
confidence: 98%